Franchisee business continuity and survival strategies : Navigating external shock in Malaysia's franchising ecosystem (Global Business Management Review (GBMR), 2025)
Franchise sector has significant contribution to local and global economic growth and development, yet franchisees' long-term viability remains uncertain in times of global crisis. The current investigation examines the impact of market orientation, franchisor assistance, and government support on franchisee survival ability in Malaysia. Data was collected from 198 Malaysian franchisees using the survey approach. The  analysis was carried out using structural equation modelling. The results demonstrated that market orientation (β=0.283, ρ